Pengaruh Kualitas Pelayanan Terhadap Peningkatan Kepuasan Pelanggan Pada Hotel Bogor - Rani Kurniasari (Widya Cipta - Jurnal Sekretari dan Manajemen, 2019)
Excellent service quality is an important factor in increasing customer satisfaction. This study aims to determine the effect of service quality on customer satisfaction in Bogor hotels. This study uses quantitative methods by distributing questionnaires to 72 hotel customers. Questionnaire calculation uses SPSS by testing the validity and reliability of each question item followed by a test of the correlation coefficient, determination coefficient and regression equation. The results of this study are that there is a significant influence on hotel customer satisfaction. SPSS calculation results obtained the determination coefficient of 95.7%, which means that the effect of service quality on customer satisfaction is 95.7% and the remaining 4.3% is influenced by other factors. Correlation coefficients obtained results of 0.978 which means that the relationship between service quality and customer satisfaction is very strong. So from the results of the correlation coefficient obtained, it was concluded that H1 was accepted which meant that there was a significant relationship between service quality and customer satisfaction. And based on the calculation of the regression equation obtained results of Y = 2.455 + 0.959X which indicates that if the value of excellent service increases 1, then the average value of customer satisfaction will increase by 0.959.